Workarounds as generative mechanisms for bottom‐up process innovation—Insights from a multiple case study - Bartelheimer, Christian; Wolf, Verena; Beverungen, Daniel (Information Systems Journal)
Abstract Workarounds are goal‐driven deviations from the standard operating procedures performed to overcome obstacles constraining day‐to‐day work. Despite starting as temporary fixes, they can become established across an organisation and trigger the innovation of processes and IT artefacts that can resolve misfits permanently. Although prior research has elicited antecedents and types of workarounds, it is not known how workarounds diffuse in an organisation and, thereby, innovating co‐workers' activities, IT artefacts, and organisational structures. The results of our multiple two‐year case study provide unique empirical insights into the diffusion of workarounds and how they can act as generative mechanisms for bottom‐up process innovation.
Keywords: Computer Networks and Communications; Information Systems; Software

Service System Innovation: An Ambidexterity Perspective - Wolf, Verena

Designing Digital Community Service Platforms for Crowd-Based Services in Urban Areas - Bartelheimer, Christian; Wolf, Verena; Langhorst, Nico; Seegers, Florian (Proceedings of the 15th International Conference on Design Science Research in Information Systems and Technology)

Understanding Smart Service Systems Transformation – A Socio-Technical Perspective - Wolf, Verena (Proceedings of the 28th European Conference on Information Systems)

Detecting Workarounds in Business Processes — A Deep Learning Method for Analyzing Event Logs - Weinzierl, Sven; Wolf, Verena; Pauli, Tobias; Beverungen, Daniel; Matzner, Martin (Proceedings of the 28th European Conference on Information Systems)

Capabilities for Ambidextrous Innovation of Digital Service - Wolf, Verena; Lüttenberg, Hedda (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

Establishing Smart Service Systems is a Challenge: A Case Study on Pitfalls and Implications - Wolf, Verena; Franke, Alena; Bartelheimer, Christian; Beverungen, Daniel (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

Transformation of Actors’ Roles in Service Systems: A Multi-Level Analysis - Wolf, Verena; Bartelheimer, Christian (16th International Research Conference in Service Management)

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)
Business Process Management is a boundary-spanning discipline that aligns operational capabilities and technology to design and manage business processes. The Digital Transformation has enabled human actors, information systems, and smart products to interact with each other via multiple digital channels. The emergence of this hyper-connected world greatly leverages the prospects of business processes – but also boosts their complexity to a new level. We need to discuss how the BPM discipline can find new ways for identifying, analyzing, designing, implementing, executing, and monitoring business processes. In this research note, selected transformative trends are explored and their impact on current theories and IT artifacts in the BPM discipline is discussed to stimulate transformative thinking and prospective research in this field.
Keywords: Business process management (BPM); Social computing; Smart devices; Big data analytics; Real-time computing; BPM life-cycle

Digitalization of Work Systems—An Organizational Routines’ Perspective - Wolf, Verena; Bartelheimer, Christian; Beverungen, Daniel (Proceedings of the 52nd Hawaii International Conference on System Sciences (HICSS-52))

Conceptualizing the Impact of Workarounds – An Organizational Routines’ Perspective - Wolf, Verena; Beverungen, Daniel (Proceedings of the 27th European Conference on Information Systems (ECIS))
Employees’ acceptance and resistance of new technology and social structure are frequently examined in Information Systems research. Resistance is expressed in various forms, including a lack of cooperation, workarounds, and physical sabotage. Workarounds, in particular, have a dual nature and can refer to both, undesirable behavior that contradicts organizational struc-ture and to desired organizational innovation. While antecedents and different forms of worka-rounds have been explored, literature has remained silent on how and why workarounds of an individual employee can affect activities performed by other employees and thereby, change work routines on an organizational level. Since employees’ day-to-day performances constitute the ostensive patterns of a routine, we argue that workarounds will not only impact performanc-es of adjacent routines, but also transform the organization as a social structure. With a prelim-inary set of qualitative data from 24 interviews, we used a multiple case study design to concep-tualize six patterns that illustrate how and why workarounds can spread through an organiza-tion. The patterns are systematized by a framework that considers three types of collaboration and two types of handoffs across routines. This first evidence points at the nature of complex desired and undesired consequences that can emerge through workarounds performed in an organization.
Keywords: Resistance; Workaround; Organizational Routines; Structuration Theory

Ambidexterity in Service Innovation Research: A Systematic Literature Review - Wolf, Verena (Proceedings of the 14th International Conference on Wirtschaftsinformatik)
Increased interconnectedness of multiple actors and digital resources in service eco-systems offer new opportunities for service innovation. In digitally transforming eco-systems, organizations need to explore and exploit innovation simultaneously, which is defined as ambidexterity. However, research on ambidextrous service innovation is scarce. We provide a systematic literature review based on the concepts of ambidexterity, offering two contributions. First, research strands are disconnected, emphasizing either exploration or exploitation of service innovation, despite an organizations’ need to accelerate innovation cycles of exploring and exploiting services. Second, a new framework for ambidextrous service innovation is provided, inspired by the dynamism and generative mechanisms of the ontologically related concept of organizational routines. The framework adopts the perspective of a mutually constitutive relationship between exploring new and exploiting current resources, activities, and knowledge. The findings remedy the scattered literature through a coherent perspective on service innovation that responds to organizations’ needs and guides future research.
Keywords: Exploration; Exploitation; Service Innovation; Organizational Routines; Ambidexterity

Smart Service Systems als Handlungsfeld einer konvergierenden Dienstleistungsforschung - Beverungen, Daniel; Bartelheimer, Christian; Wolf, Verena (Digitale Dienstleistungsinnovationen – Smart Services agil und kundenorientiert entwickeln)

DIN SPEC 33453:2019-09, Entwicklung digitaler Dienstleistungssysteme - Post, Till; Heuermann, Aaron; Wiesner, Stefan; Olschewski, Detlef; Maaß, Wolfgang; Klatt, Rüdiger; Jussen, Philipp; Ragab, Sherif; Senderek, Roman; Höckmayr, Benedikt; Schulz, Thomas; Meyer, Kyrill; et al.

Service (Systems) Engineering für die Produktion - Lüttenberg, Hedda; Wolf, Verena; Beverungen, Daniel (Service Engineering)

Dienstleistungssysteme erfolgreich digital transformieren - Beverungen, Daniel; Wolf, Verena; Bartelheimer, Christian (Service Business Development. spot.on marketing - Der Newsletter für Marketing und Business Development)

The Impact of Process Automation on Manufacturers’ Long-Term Knowledge - Gernreich, Chris; Wolf, Verena; Bartelheimer, Christian; Prinz, Christopher (Proceedings of the 39th International Conference on Information Systems)

Digitale Transformation von Dienstleistungssystemen - Beverungen, Daniel; Wolf, Verena; Bartelheimer, Christian (Service Business Development)

Recombinant Service Systems Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Business & Information Systems Engineering)
Although many methods have been proposed for engineering service systems and customer solutions, most of these approaches give little consideration to recombinant service innovation. Recombinant innovation refers to reusing and integrating resources that were previously unconnected. In an age of networked products and data, we can expect that many service innovations will be based on adding, dissociating, and associating existing value propositions by accessing internal and external resources instead of designing them from scratch. The purpose of this paper is to identify if current service engineering approaches account for the mechanisms of recombinant innovation and to design a method for recombinant service systems engineering. In a conceptual analysis of 24 service engineering methods, the study identified that most methods (1) focus on designing value propositions instead of service systems, (2) view service independent of physical goods, (3) are either linear or iterative instead of agile, and (4) do not sufficiently address the mechanisms of recombinant innovation. The paper discusses how these deficiencies can be remedied and designs a revised service systems engineering approach that reorganizes service engineering processes according to four design principles. The method is demonstrated with the recombinant design of a service system for predictive maintenance of agricultural machines.
Keywords: Service engineering; Recombinant innovation; (Product-)service system; Design science research; New service development

Recombinant Service System Engineering - Beverungen, Daniel; Lüttenberg, Hedda; Wolf, Verena (Proceedings der 13. Internationalen Tagung Wirtschaftsinformatik (WI 2017))
Although many methods have been proposed for engineering services and customer solutions, most of these approaches give little consideration to recombinant service innovation. In an age of smart products and smart data, we can, however, expect that many of future service innovations need to be based on adding, transferring, dissociating, and associating existing value propositions. The purpose of this paper is to outline what properties constitute recombinant service innovation and to identify if current service engineering approaches fulfill these properties. Based on a conceptual in-depth analysis of 24 service engineering methods, we identify that most methods focus on designing value propositions instead of service systems, view service independent of physical goods, are linear or iterative, and incompletely address the mechanisms of recombinant innovation. We discuss how these deficiencies can be remedied and propose a first conceptual model of a revised se rvice system engineering approach.
Keywords: Service engineering; recombinant innovation; (product - )service system; literature analysis; new service development